2021
DOI: 10.1136/gpsych-2021-100576
|View full text |Cite|
|
Sign up to set email alerts
|

Discordance between family report and clinical assessment of suicide attempts: a prospective study from the emergency department

Abstract: BackgroundDeveloping accurate identification methods for individuals with suicide attempts and providing them with follow-up care and supports can be a vital component of all comprehensive suicide prevention strategies. However, because of the difficulties concerning one’s intentions behind injurious behaviour, identifying suicide attempts is a challenge for families and clinicians.AimsThe aim of this study was to investigate the differences between family report and clinical assessment for suicide attempts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…This is in line with the literature that shows low agreement between self-reports and clinician assessments regarding SI [49], with high rates of false positives registered in self-report measures compared to clinical assessment [50]. Moreover, previous studies reported different agreements between the family report and clinical assessment [51]. However, other studies report that participants feel more comfortable disclosing information on suicide-related topics through the relative anonymity of a self-rating scale [52,53].…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with the literature that shows low agreement between self-reports and clinician assessments regarding SI [49], with high rates of false positives registered in self-report measures compared to clinical assessment [50]. Moreover, previous studies reported different agreements between the family report and clinical assessment [51]. However, other studies report that participants feel more comfortable disclosing information on suicide-related topics through the relative anonymity of a self-rating scale [52,53].…”
Section: Discussionsupporting
confidence: 89%
“… 4 However, in contrast, a recent study found a relatively low reported rate of suicide attempts by family members in China, which could suggest that recognising suicidal risks remains a crucial challenge for suicide prevention. 5 The Ministry of Education of the People’s Republic of China 6 has recognised the urgent need for promoting mental health services to reduce suicidal risks among Chinese students and advocated a strong collaborative partnership between schools, families and mental health services to improve the ability to intervene in psychological crises among students.…”
Section: Introductionmentioning
confidence: 99%